Stain-Free technology as a normalization tool in Western blot analysis - Gürtler, Anne; Kunz, Nancy; Gomolka, Maria; Hornhardt, Sabine; Friedl, Anna A.; McDonald, Kevin; Kohn, Jonathan E.; Posch, Anton (Analytical biochemistry, 2013)
Western blots are used to specifically measure the relative quantities of proteins of interest in complex biological samples. Quantitative measurements can be subject to error due to process inconsistencies such as uneven protein transfer to the membrane. These non-sample-related variations need to be compensated for by an approach known as normalization. Two approaches to data normalization are commonly employed: housekeeping protein (HKP) normalization and total protein normalization (TPN). In this study, we evaluated the performance of Stain-Free technology as a novel TPN tool for Western blotting experiments in comparison with glyceraldehyde-3-phosphate dehydrogenase (GAPDH) as a representative of the HKP normalization strategy. The target protein (TP) used for this study was MCM7, a DNA licensing replication factor, which was shown previously to be down-regulated by 20% in irradiated lymphoblastoid cell lines (LCLs). We studied the regulation of MCM7 with a multiplex Western blotting approach based on fluorescently labeled secondary antibodies and found that Stain-Free technology appears to be more reliable, more robust, and more sensitive to small effects of protein regulation when compared with HKP normalization with GAPDH. Stain-Free technology offers the additional advantages of providing checkpoints throughout the Western blotting process by allowing rapid visualization of gel separation and protein transfer.